Pasar Monopoli dalam Pandangan Islam - El Munawwarah (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT STIE-GRAHA KARYA MUARA BULIAN, 2021)
Monopoly in general is the control by one party of a certain type of goods. In Indonesia, it can be said that monopolistic practices are not all harmful. There are even some monopolistic practices that are actually very positive, such as monopoly on a number of important assets, such as: PLN, PAM, Pertamina and so on. The monopoly practice carried out by the government refers to the mandate of the 1945 Constitution article 33. Meanwhile, the prohibited monopoly practice is a monopoly that can harm the community, such as monopoly on food sources with the aim of seeking one-sided profit. Where the source of basic needs like that is needed by the community in general and is urgent. In the view of business law in Indonesia, monopolistic practices are strictly prohibited, as stated in Law no. 5 of 1999. However, in the view of some scholars, monopoly is allowed, provided that there is no ikhtikar (excessive profit-taking). In the view of Islamic business, monopolistic practices are the main cause of chaos in the economic order. Monopoly practices in the business world tend to be motivated by egoism and want to seek profits unilaterally. This of course will be very disturbing to the community. To reduce monopolistic practices, the government and society can take proactive steps to reduce monopolistic practices. The government must take firm action against institutions or people who practice monopolistic practices that can harm the public at large. Meanwhile, the public can report to the competent authorities if they see a monopoly practice that causes economic chaos.